Rough hollow mesoporous silica nanoparticles as carrier for agarwood oil to treat cancer cells - Khairudin, Nurul Hafizah; Ahmad Nor, Yusilawati; Hashim, Yumi Zuhanis Has-Yun (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Natural products such as agarwood oil (AO) are found to exhibit potential anticancer properties. They provide safer and better alternative to the conventional drugs used in chemotherapy treatment. However, due to the limitation of AO in terms of volatility, stability and solubility in water, a suitable carrier is needed to enhance the performance of the essential oil. Mesoporous silica nanoparticles are found to be promising carrier for AO as it is biocompatible, hydrophilic, possesses high stability, high total surface area and high pore volume properties which can reduce the limitations possessed by AO. Rough mesoporous hollow silica (RMHS) nanoparticles were used in this study as the particles known to have high loading capacity due to its pores and rough surface. By using ethanol as solvent, the ratio of AO to RMHS 20:1 with loading time of 24 hour has successfully achieved high loading efficiency as much as 62.79%. Successful loading of AO in RMHS was confirmed by Fourier transform infrared (FTIR). Sustained release of AO from RMHS has been observed, with release up to 63.8% after 72 hours. Cell viability assay (CVA) by using MTT assay showed that RMHS loaded with AO (RMHS-AO) was able to reduce the viability of MCF-7 cells up to 73% reduction after 48 hours of treatment.